Model-Free Predictive Anti-Slug Control of a Well-Pipeline-Riser - Christer Dalen (Modeling, Identification and Control, 2016)
Simplified linearized discrete time dynamic state space models are developed for a 3-phase well-pipeline-riser and tested together with a high fidelity dynamic model built in K-Spice and LedaFlow. In addition the Meglio pipeline-riser model is used as an example process. These models are developed from a subspace algorithm, i.e. Deterministic and Stochastic system identification and Realization (DSR), and implemented in a Model Predictive Controller (MPC) for stabilizing the slugging regime. The MPC, LQR and PI control strategies are tested.